2014
DOI: 10.4236/ojcd.2014.41010
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Skin Necrosis after Enoxaparin Treatment

Abstract: Subcutaneous low molecular weight heparin (LMWH) injection is a prophylactic treatment for deep vein thrombosis after surgery in lower limb before the patient is fully ambulated. This treatment is usually safe. One of the major and rare complications of the LMWH injection is thrombocytopenia, which is usually self-limiting. We present a rare case of patient with thrombocytopenia, induced by subcutaneous injection of LMWH (enoxaparin) that was complicated with a large hematoma at the injection site with subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Along with bleeding risk, rare cutaneous side effects have been reported in the literature [2] , [3] . Enoxaparin-induced skin necrosis, as seen in our case, has been associated with grave consequences, including death [4] , [5] .…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Along with bleeding risk, rare cutaneous side effects have been reported in the literature [2] , [3] . Enoxaparin-induced skin necrosis, as seen in our case, has been associated with grave consequences, including death [4] , [5] .…”
Section: Introductionsupporting
confidence: 51%
“…We are aware of 3 prior case reports in the literature documenting Lovenox-induced skin necrosis in the setting of TKA. In the case by Maruan et al [5] , thrombocytopenia was found on POD 4, followed by skin necrosis developing on POD 5. The LMWH was discontinued but there was no mention of starting aspirin or a direct thrombin inhibitor.…”
Section: Discussionmentioning
confidence: 92%
“…Although rare, enoxaparin-induced skin necrosis is a very serious complication, with reported fatalities due to development of sepsis 7 8. Additionally, a fatality was reported where a patient developed thrombocytopenia, leading to a large abdominal haematoma, with subsequent development of necrosis and septic shock 9…”
Section: Introductionmentioning
confidence: 99%